Hétérogénéité et valeur du discours littéraire - Stéphane Bikialo (Corela)
This article examines the place and function of the metalinguistic and heterogeneity in the value of literary discourse. From the hypothesis by J. Rey-Debove on literature as mode of as I say, reformulated in light of the work of J. Authier-Revuz, in the way I say X' (where X’ is a sign modalisation autonymique), the article evokes (contemporary) works where language is "reminded" before attaching the literary discourse genres (novel and poetry) and their respective heterogeneity in dregs with the genres of daily speeches.